A phase 3, open-label, randomized trial to evaluate the safety and efficacy of levofloxacin inhalation solution (APT-1026) versus tobramycin inhalation solution in stable cystic fibrosis patients - Elborn, J. Stuart; Geller, David E.; Conrad, Douglas; Aaron, Shawn D.; Smyth, Alan R.; Fischer, Rainald; Kerem, Eitan; Bell, Scott C.; Loutit, Jeffery S.; Dudley, Michael N.; Morgan, Elizabeth E.; VanDevanter, Donald R.; et al. (Elsevier, 2015)
Background: Inhaled antibiotics are standard of care for persons with cystic fibrosis (CF) and chronic Pseudomonas aeruginosa airway infection. APT-1026 (levofloxacin inhalation solution, LIS) is fluoroquinolone in development. We compared the safety and efficacy of LIS to tobramycin inhalation solution (TIS) in persons ≥12 years old with CF and chronic P. aeruginosa infection. Methods: This multinational, randomized (2:1), non-inferiority study compared LIS and TIS over three 28-day on/off cycles. Day 28 FEV1 % predicted change was the primary endpoint. Time to exacerbation and patient-reported quality of life superiority were among secondary endpoints. Results: Baseline demographics for 282 subjects were comparable. Non-inferiority was demonstrated (1.86% predicted mean FEV1 difference [95% CI −0.66 to 4.39%]). LIS was well-tolerated, with dysguesia (taste distortion) the most frequent adverse event. Conclusions: LIS is a safe and effective therapy for the management of CF patients with chronic P. aeruginosa.